Analisis Penerapan Intensifikasi Pajak Bumi Dan Bangunan Sebagai Upaya Optimalisasi Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Kota Bekasi Tahun 2020 - Ira Septiyani; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The instability in the realization of Land and Building Tax (PBB)revenue to Bekasi City Regional Tax receipts is on the rise. One of the reasons is the weakening of the community's economy amidst the impact of the Covid-19 pandemic. The level of compliance and public awareness as taxpayers are still very low, exacerbated by the lack ofsocialization about the importance of paying taxes, especially from the Land and Building Tax sector. Based on this background, this research aims to analyze the implementation of Land and Building Taxintensification as an effort to optimize local revenue at the Bekasi City Bapenda in 2020, obstacles in the implementation of Land and Building Tax intensification as an effort to optimize local revenue at the Bekasi City Bapenda in 2020, and what efforts can be optimizedin the implementation of the Land and Building Tax intensification oflocal revenue at the Bekasi City Bapenda in 2020. This research employs Kustiawan's theory of tax intensification, according to which the implementation of tax intensification can be pursued through three aspects, namely: Institutional Aspects, Management Aspects, and Personnel Aspects. The methodology used is descriptive qualitative. Data collection in this study was carried out through observation, documentation, and interviews. The results of this study indicate that the target has not been achieved and the Land and Building Tax realization revenue has not stabilized againstthe predetermined local tax target, where the percentage experiencedinstability in 2018 was only 90.66%, in 2019 it decreased by 77.41%,and in 2020 it was 96. 21% but nominally the lowest figure is from the previous year, which was only Rp. 1,585,937,678,852.00, in 2020.There are still frequent data discrepancies with actual conditions, the weakening of the community's economy, and the lack of awareness and socialization society is a limiting factor. Meanwhile, with the issuance of the Bekasi Mayor's temporary policy Number 973.7/Kep.298-Bapenda/V/2020 as an incentive for the impact of the Covid-19 Extraordinary Event status, conducting more thorough socialization, and optimization of combing operations in each region can be done asan effort to optimizing the rate of local tax revenue in the implementation of PBB intensification as an effort to optimize localrevenue at the Bekasi City Bapenda 2020